High energy efficiency and high power density aluminum‐air flow battery. (28th April 2020) - Wen, Hejing; Liu, Zhongsheng; Qiao, Jia; Chen, Ronghua; Zhao, Ruijie; Wu, Jianchun; Qiao, Guanjun; Yang, Jianhong
Summary: Aluminum‐air battery (AAB) is a very promising energy generator for electric vehicles (EVs) due to its high theoretical capacity and energy density, low cost, earth abundance, environmental benignity and rapid refuel. In this study, the practical energy efficiency and power density of AAB are improved by optimizing its factors, such as anode‐cathode distance, operation temperature, electrolyte flow rate and the atmosphere. Under air atmosphere, the peak power density reaches 381 mW cm −2, and the optimum output power density is 258 mW cm −2 with the anode efficiency of 90.9% and energy efficiency of 44.4%; and under pure O2 atmosphere, the peak power density is up to 545 mW cm −2, and the optimum output power density is 430.5 mW cm −2 with the anode efficiency of 94.2% and energy efficiency of 42.6%. These results are promising to constitute a foundation for future development of Al‐air battery systems for EVs. Highlights There is rare literature on the influence of ACD and electrolyte flow rate on Al‐air battery performances. The optimum parameters for Al‐air flow battery are operating at 60°C with parameters of ACD of 0.5 mm, electrolyte flow rate of 15 mL min −1 under pure O2 atmosphere. Pure O2 atmosphere can help to keep high energy efficiency at high power density for Al‐air flow battery due to the increased oxygen solubility, but slightly reduced anode efficiency. Under pure O2 atmosphere, the peak power density is up to 545 mW cm −2, the anode efficiency reaches 96.2%. The optimum output of power density is 430.5 mW cm −2 with the energy efficiency of 42.6%. Abstract : The influences of anode‐cathode distance, temperature, electrolyte flow rate and atmosphere on the performances of aluminum‐air battery were systematically investigated and optimized. Under pure O2 atmosphere, the peak power density is up to 545 mW cm ‐2, and the high efficient output power density is 430.5 mW cm ‐2 with the anode efficiency of 94.2% and energy efficiency of 42.6%.